Analisis Kandungan Merkuri (Hg) Pada Terumbu Karang Akibat Pertambangan Emas Rakyat Di Kawasan Teluk Pelangan - Selindungan Kecamatan Sekotong - Irna Il Sanuriza (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2017)
Activities of disposal recidue mining contain of Mercury (Hg) acumulated from the citizen gold mining operation at Pelangan-Selindungan, directly throwing to river and streaming down to the sea, it can caused coastal enviromments pollution including coral reef ecosystem. The aim of the research for determining the heavy metal content of mercury (Hg) on coral reefs at the region Pelangan-Selindungan gulf Sekotong. This is a descriptive exploratory research that was taken at Pelangan-Selindungan gulf Sekotong and Gili Meno as a region control. AAS analysis of coral reef was conducted at Analytical Laboratory of Mataram University in May-August 2013. The result indicated that coral reefs at the gulf Pelangan-Selindungan had been contaminated but it still under the quality standard limits.